Single-cut genome editing restores dystrophin expression in a new mouse model of muscular dystrophy - Amoasii, Leonela; Schmidt, Florian; Grimm, Dirk (Science translational medicine, 2017)
Duchenne muscular dystrophy (DMD) is a severe, progressive muscle disease caused by mutations in the dystrophin gene. The majority of DMD mutations are deletions that prematurely terminate the dystrophin protein. Deletions of exon 50 of the dystrophin gene are among the most common single exon deletions causing DMD. Such mutations can be corrected by skipping exon 51, thereby restoring the dystrophin reading frame. Using clustered regularly interspaced short palindromic repeats/CRISPR-associated 9 (CRISPR/Cas9), we generated a DMD mouse model by deleting exon 50. These ΔEx50 mice displayed severe muscle dysfunction, which was corrected by systemic delivery of adeno-associated virus encoding CRISPR/Cas9 genome editing components. We optimized the method for dystrophin reading frame correction using a single guide RNA that created reframing mutations and allowed skipping of exon 51. In conjunction with muscle-specific expression of Cas9, this approach restored up to 90% of dystrophin protein expression throughout skeletal muscles and the heart of ΔEx50 mice. This method of permanently bypassing DMD mutations using a single cut in genomic DNA represents a step toward clinical correction of DMD mutations and potentially those of other neuromuscular disorders.
Available in PMC 2018 January 02
Gesehen am 23.05.2018
This article has been corrected